Gegen Qinlian Decoction Treats Diarrhea in Piglets by Modulating Gut Microbiota and Short-Chain Fatty Acids - Liu, Chang-Shun; Liang, Xiao; Wei, Xiao-Han; Jin, Zhen; Chen, Fei-Long; Tang, Qing-Fa; Tan, Xiao-Mei (Frontiers in Microbiology, 2019)
Gut microbiota and its metabolites, short-chain fatty acids (SCFAs), play important roles in diarrheal diseases. Gegen Qinlian decoction (GQD), a Chinese herb formula, has been widely used to treat infectious diarrhea for centuries. However, little is known about the mechanism underlying its efficacy and whether it is mediated by gut microbiota and SCFAs. In this study, the composition of gut microbiota from bacterial diarrheal piglets was assessed using 16S rRNA analysis. The concentrations of fecal SCFAs were determined using a gas chromatography-mass spectrometer. The expression of mucosal pro-inflammatory cytokines in the colon was ascertained. Results showed that GQD reverses the reduction in the richness of gut microbiota, changes its structure, and significantly increases the relative abundances of SCFA-producing bacteria, including Akkermansia, Bacteroides, Clostridium, Ruminococcus, and Phascolarctobacterium. Moreover, GQD increased the levels of fecal SCFAs, including acetic acid, propionic acid, and butyric acid. GQD thus attenuates diarrhea in piglets. Further, our results suggest that the SCFAs could help to attenuate mucosal pro-inflammatory responses following GQD treatment by inhibiting histone deacetylase and the NF-κB pathway. We thus suggseted that gut microbiota play an important role during diarrhea treatment, an effect may be promoted by the GQD-induced structural changes of the gut microbial community and production of SCFAs. The increased levels of SCFAs probably provide further help to attenuate mucosal inflammation and diarrhea. In conclusion, our study might provide evidence that GQD treats diarrhea maybe involved in modulating gut microbiota and increasing SCFA levels.